AI-Driven Managed Services: Automating Tier 1 to Tier 3 Operations for Scalable Customer Support (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The increasing complexity of IT services and the demand for faster issue resolution have accelerated the adoption of AI in managed services. This paper explores the deployment of AI-driven managed services to automate Tier 1 to Tier 3 operations, focusing on scalable customer support models. The research discusses the role of AI in predictive issue detection, natural language processing (NLP) for chatbot-based assistance, and automated ticket management. It also presents real-world examples where AI-enabled systems have reduced downtime, improved service levels, and optimized operational costs. The paper concludes with recommendations for implementing AI-driven managed services, including governance models, training frameworks, and best practices for aligning AI initiatives with business outcomes.